A Fast and robustColor Image Encryption Scheme by Huffman Compression, 5D Chaotic Map and DNA Encoding - Navaneethan, S.; Kalamathipriya, G.; Keyasudeen, M. S. Mohamed; Parthiban, K. (Journal of Graphic Era University, 2024)
In the era of information technology, securing the real-time digital image is the greatest challenge especially colour image. In this paper, a colour image encryption scheme is introduced to secure the image based on compression-then-encryption concept. Theproposed method is a hybrid combination of the Chaos techniques for key generation, Huffman Encoding/compression for compression and avoiding colour decomposition, scrambling for more confusion and DNA Encoding for reducing storage size. In order to enhance security, scrambled data are converted to the Deoxyribonucleic acid (DNA) sequence, make ADD operation and apply the complementary rules to attain the cipher image. Experimental results have been proved as robustness, accurate and high security against attacks, malicious attacks, differential attacks and statistical attacks. Furthermore, results show that the time speed is faster minimum storage space than the existing colour image encryption scheme.